Politics of development in Terengganu (1999-2013) / Ilyas Abdullah - Abdullah, Ilyas (Universiti Teknologi MARA, 2022)
The political culture of the Malays in Terengganu prior to the 10th General Election was very much in support of UMNO-BN. The results of the GE-10 showed that UMNO and the opposition PAS particularly have an equal opportunity to form the state government in Terengganu. The findings show that development is the main factor that influenced the Malay political culture in Terengganu in the pre- and post-GE-10 periods. However, in post GE-10, development is no longer construed as merely for convenience of comfort, but to be integrated with the principles of justice as well.